2020
DOI: 10.1177/1060028020922492
|View full text |Cite
|
Sign up to set email alerts
|

Clearance Confusion: An Exploratory Analysis of Inpatient Dosing Discordances Between Renal Estimating Equations

Abstract: Background: Numerous equations exist for estimating renal clearance for drug dosing, and discordance rates may be as high as 40% in certain populations. However, the populations and types of equations used in these studies may not be generalizable to broader pharmacy practice. Objectives: To determine the dosing discordance rate between Cockcroft-Gault (C-G), Chronic Kidney Disease Epidemiology (CKD-EPI), and Modification of Diet in Renal Disease (MDRD) equations in a community hospital population. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Both equations are now necessary for medication dose modification because an increasing number of medications have been approved in recent years with labeling recommending dose adjustment by CKD-EPI or MDRD in lieu of the more traditional C-G. 7,11 Unfortunately, studies that analyze dose discordance rates between the variants of the C-G equation and the 2 GFR equations suggest prevalence rates as high as 40%, and discordance rates appear to be particularly high in the elderly. 18,29,30,31 Further research is necessary before the use of a single equation is adopted by the pharmaceutical industry or medical practitioners. Simultaneously, further research into the way that multiple estimates affect clinical decision-making may have the potential to improve the way EMRs affect renal dosing decisions in inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Both equations are now necessary for medication dose modification because an increasing number of medications have been approved in recent years with labeling recommending dose adjustment by CKD-EPI or MDRD in lieu of the more traditional C-G. 7,11 Unfortunately, studies that analyze dose discordance rates between the variants of the C-G equation and the 2 GFR equations suggest prevalence rates as high as 40%, and discordance rates appear to be particularly high in the elderly. 18,29,30,31 Further research is necessary before the use of a single equation is adopted by the pharmaceutical industry or medical practitioners. Simultaneously, further research into the way that multiple estimates affect clinical decision-making may have the potential to improve the way EMRs affect renal dosing decisions in inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…information, the reader is referred to a recent paper 19 that found a widespread dosing discordance rate between the CG, MDRD and CKD-EPI equations in patients.…”
Section: Accepted Articlementioning
confidence: 99%
“…Using the CKD‐EPI equation for measuring GFR in phase I studies may help in harmonizing CKD staging, population PK (PopPK) analyses, and dosing by estimated renal function. 18 For more information, the reader is referred to a recent paper 19 that found a widespread dosing discordance rate among the CG, MDRD, and CKD‐EPI equations in patients.…”
Section: Assessment Of Renal Functionmentioning
confidence: 99%
“…Numerous research studies have indicated that significant differences exist when comparing CG CrCl and the GFR equations when estimating renal function for the purposes of making dosage adjustments. 9,10 Discordance with drug dosage recommendations have been reported in rates ranging from 20% to 67% when comparing MDRD estimated GFR (eGFR) to CrCl. 11 Despite this, the National Institute of Diabetes and Digestive and Kidney Diseases Laboratory Working Group recommends eGFR as an alternative to CrCl for drug dosing, and several recently approved medications include dosage recommendations based on eGFR.…”
Section: Introductionmentioning
confidence: 99%